Alih Kode dan Campur Kode dalam Transaksi Jual Beli di Pasar Tengah Pontianak - Rusmidah, Rusmidah; Simanjuntak, Hotma; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to describe code-switching and code-mixing found in buying and selling transactions in Pontianak Central Market, based on the types and causes of occurrence. The benefit of this research is to add insight into the code, code switching and mixing in buying and selling transactions in Pontianak Central Market. The method in this research is descriptive method in the form of qualitative research. The technique used is observation technique or direct observation. Data collection used tapping technique and free listening technique. Tapping is done with a recording device in the form of portable digital audio voice recording. Techniques to test the validity of data in this study are observation persistence, triangulation, and discussion with the supervisor. Based on the data analysis, this research concludes that there are 63 data in the form of code switching and 48 data in the form of inward code mixing and outward code mixing.